2015
DOI: 10.1016/j.celrep.2015.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Anti-estrogen Resistance in Human Breast Tumors Is Driven by JAG1-NOTCH4-Dependent Cancer Stem Cell Activity

Abstract: SummaryBreast cancers (BCs) typically express estrogen receptors (ERs) but frequently exhibit de novo or acquired resistance to hormonal therapies. Here, we show that short-term treatment with the anti-estrogens tamoxifen or fulvestrant decrease cell proliferation but increase BC stem cell (BCSC) activity through JAG1-NOTCH4 receptor activation both in patient-derived samples and xenograft (PDX) tumors. In support of this mechanism, we demonstrate that high ALDH1 predicts resistance in women treated with tamox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
204
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(217 citation statements)
references
References 17 publications
12
204
1
Order By: Relevance
“…Estrogen may exert influence on stem cells via paracrine mechanisms because CD44 C CD24 K and ALDH C CSCs have been shown to lack expression of ER or express it at very low levels (Morimoto et al 2009, Harrison et al 2013, Simões et al 2015. Similar to what happens in the normal mammary gland, it has been suggested that estrogen can promote CSC activity of ER K BCSCs by inducing the secretion of paracrine growth factors from ER C cells.…”
Section: Estrogen and Bcscsmentioning
confidence: 77%
See 2 more Smart Citations
“…Estrogen may exert influence on stem cells via paracrine mechanisms because CD44 C CD24 K and ALDH C CSCs have been shown to lack expression of ER or express it at very low levels (Morimoto et al 2009, Harrison et al 2013, Simões et al 2015. Similar to what happens in the normal mammary gland, it has been suggested that estrogen can promote CSC activity of ER K BCSCs by inducing the secretion of paracrine growth factors from ER C cells.…”
Section: Estrogen and Bcscsmentioning
confidence: 77%
“…Moreover, it was established that inhibition of the Notch signalling pathway reduces BCSC activity, and that the Notch4 receptor has a key role in controlling BCSCs (Harrison et al 2010). Recently, our group demonstrated that treating ER C breast cancer cells with endocrine therapies leads to increased Jag1-Notch4 signalling and that combining endocrine therapies with a Notch pathway inhibitor can prevent BCSC enrichment induced by endocrine therapies (Simões et al 2015). Our results suggest that inhibition of Notch signalling can help overcoming endocrine therapy resistance and might prevent recurrence in ER C breast cancer.…”
Section: Cd24mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Simões et al demonstrated that anti-estrogen therapy using Tamoxifen or Fulvestrant, increased the activity of the BCSCs though activation of NOTCH4-JAG1 axis (88). The same group also showed that a hormone therapy combined with NOTCH4 inhibition, using γ-secretase inhibitor RO4929097, might abrogate anti-estrogen therapy resistance.…”
Section: Perspectives For Bcscs: the Futurementioning
confidence: 86%
“…For example, cases of multiple myeloma have displayed abnormal signaling in response to elevated levels of Hedgehog ligand secreted by tumor stromal cells, [9] and upregulated Notch4 signaling has been implicated in drug-resistant breast CSC activity. [10] Like SCs, CSCs are able to repair damaged DNA more quickly and overexpress drug-efflux pumps such as ATP-binding cassette (ABC) transporters. In a glioblastoma model, aberrant Akt signaling contributed to overactivation of the ABC transporter ABCG2 in CSCs, leading to increased drug expulsion and rendering them resistant to mitoxantrone.…”
Section: Introductionmentioning
confidence: 99%